2022
DOI: 10.21203/rs.3.rs-1364399/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effectiveness of local steroid injection for the treatment of breast-limited idiopathic granulomatous mastitis: A randomized controlled clinical trial study

Abstract: Background: Idiopathic granulomatous mastitis (IGM) is a rare non-specific inflammatory breast disease and is usually considered a kind of autoimmune disease. There are several controversies regarding its standard treatment. We aimed to evaluate the efficacy of local corticosteroid injection for the treatment of breast-limited idiopathic granulomatous mastitis.Methods: This randomized prospective clinical trial study evaluated the clinical response rate of local steroid injection to treat breast-limited IGM in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A study involving 156 patients who received 5 days of in-patient steroid therapy before excisional surgery revealed that only 5.1% of them experienced recurrence, a signi cantly lower rate compared to those who solely received prednisone (p < 0.01) (18). In addition to systemic steroid administration, the utilization of topical steroid application and intralesional injections has also shown promising results (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…A study involving 156 patients who received 5 days of in-patient steroid therapy before excisional surgery revealed that only 5.1% of them experienced recurrence, a signi cantly lower rate compared to those who solely received prednisone (p < 0.01) (18). In addition to systemic steroid administration, the utilization of topical steroid application and intralesional injections has also shown promising results (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The administration of corticosteroids prior to surgery for large lesions improves the aesthetic outcome. Intralesional corticosteroid injection and topical corticosteroid can be used to treat IGM patients with primarily skin changes or who have experienced systemic corticosteroid side effects [ 11 , 14 ]. The principal drawback of corticosteroid therapy is its side effects, which manifest themselves primarily after long-term, high-dose use.…”
Section: Discussionmentioning
confidence: 99%